FIXATION OF REMOVABLE DENTURES ON COMPLETELY EDENTULOUS JAWS USING IMPLANTS - Ismoilov IIhomjon Xurboevich, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
Treatment by means of tooth implants can provide toothless patients with steadier alternative to full tooth artificial limbs. Basically at various clinical situations tooth implants varying from 3.0 mm to 7.0 mm in diameter are used. This range limits the use of implant therapy in many patients with pronounced bone atrophy. Occurrence in the market of SDI (Small Dental Implants), implants of small diameter has expanded these possibilities. These implants are made of titanium alloy which is the strongest in its class. The sparing report of installation is one of the main distinctive features of the mini-implant system which makes this system unique and allows preserving the function and stability of artificial limbs for many years.